Upregulated IL-6 Indicates a Poor COVID-19 Prognosis: A Call for Tocilizumab and Convalescent Plasma Treatment - Wu, Jian; Shen, Jiawei; Han, Ying; Qiao, Qinghua; Dai, Wei; He, Bangshun; Pang, Rongrong; Zhao, Jun; Luo, Tao; Guo, Yanju; Yang, Yang; Wu, Qiuyue; et al. (Frontiers in Immunology, 2021)
A comprehensive understanding of the dynamic changes in interleukin-6 (IL6) levels is essential for monitoring and treating SARS-Cov-2 infected patients. By analyzing the correlations between IL6 levels and health conditions, underlying diseases, several key laboratory detection indexes, and the prognosis of 1,473 COVID-19 patients, the role of IL6 during a SARS-CoV-2 infection was demonstrated. Our results indicated that IL6 levels were closely related to age, sex, body temperature, oxygen saturation of blood (SpO2), and underlying diseases. As a stable indicator, the changes in IL6 levels could indicate the inflammatory conditions during a virus infection. Two specific treatments; i.e., tocilizumab and convalescent plasma therapy, decreased the level of IL6 and relieved inflammation. Convalescent plasma therapy has an important role in critical COVID-19 patient therapy. We also found that patients with IL6 levels that were 30-fold higher than the normal level had a poor prognosis compared to patients with lower levels of IL6.